Environmental injustice in the privatization of Brazilian sanitation: an empirical analysis - Bermann, Celio; Hermsdorff, Sonia Maria Gaspar Lontro (Frontiers in Water, 2024)
This study analyzes whether the low rate of universalizing water supply and sanitation services in Brazil is related to the low participation of private companies in the concession of these services in municipalities in the country. To this end, it discusses basic sanitation in Brazil and its current scenario, its problems from the point of view of environmental injustice, and the existing public/private conflicts. The empirical analysis conducted a data survey of 8 municipalities defined in 4 population groups, comparing data from 13 operational, efficiency, quality, and cost indicators of the services provided. Each population group compared two municipalities providing water and sewerage services, one provided by a public company and the other by a private company. The compared data were from 2021, obtained through the Brazilian National Sanitation Information System (SNIS). As a result of the comparative analyses, it was shown that the performance of public companies was more positive for most indicators, compared to private companies. It is concluded that the main challenge to overcome the social and environmental injustice resulting from the deficit in basic sanitation coverage lies in the promotion of public management instruments that enable the articulation of public and private investments in the expansion of basic sanitation services, in the improvement of the quality of services with the inclusion of social control through popular participation.